Aplikasi Simpan Pinjam Koperasi Pada PT. Primantara Berbasis Mobile Menggunakan Algoritma FIFO - Umniy Salamah; Andi Purnomo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Cooperatives have a very important role at the moment, because cooperatives provide many benefits to their members. One of the goals of the operation of the cooperative is as an alternative means of borrowing money. PT. Cooperative System Primantara which is run at this time is still using book media or using Microsoft Excel. The lending process which is still done manually sometimes makes it difficult for employees to apply for loans, therefore applications are needed to overcome these problems. The savings and loan cooperative application was built using the Android and PHP programming languages with MySQL Databse and applied the FIFO algorithm to the cooperative system. By building a savings and loan cooperative application, it can facilitate cooperative units and employees so that employees do not experience difficulties when applying for loans and easily obtain information about the remaining installments. The results of this study are the application of savings and loan cooperatives which will make it easier for employees and also cooperative units in conducting transactions within the cooperative PT. Primantara.